2018
DOI: 10.1103/physrevb.97.035143
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and magnetic properties of the half-metallic ferrimagnetMn2VAlprobed by soft x-ray spectroscopies

Abstract: We have studied the electronic structure of ferrimagnetic Mn2VAl single crystals by means of soft X-ray absorption spectroscopy (XAS), X-ray absorption magnetic circular dichroism (XMCD) and resonant soft X-ray inelastic scattering (RIXS). We have successfully observed the XMCD signals for all the constitute elements. The Mn L2,3 XAS and XMCD spectra are reproduced by spectral simulations based on density-functional theory, indicating the itinerant character of the Mn 3d states. On the other hand, the V 3d ele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 54 publications
3
16
1
Order By: Relevance
“…All the XAS spectra shown in Figure 5 exhibit two main lines without fine structures at the Mn L 3,2 -absorption edges. A spectral hump, which is expected to appear at approximately 645 eV for the ordered L2 1 phase of Mn 2 VAl [19,21,32], is missing in the present data. It is consistent with the small volume fraction of the ordered phases in the samples, as evidenced by the present TEM images and supported by the previous X-ray diffraction experiment [26,27].…”
Section: Resultscontrasting
confidence: 76%
See 3 more Smart Citations
“…All the XAS spectra shown in Figure 5 exhibit two main lines without fine structures at the Mn L 3,2 -absorption edges. A spectral hump, which is expected to appear at approximately 645 eV for the ordered L2 1 phase of Mn 2 VAl [19,21,32], is missing in the present data. It is consistent with the small volume fraction of the ordered phases in the samples, as evidenced by the present TEM images and supported by the previous X-ray diffraction experiment [26,27].…”
Section: Resultscontrasting
confidence: 76%
“…The XMCD for Sample C is also caused by Factor II; however, the situation is different from that in Sample D. In Sample C, the clusters of the L2 1 and B2 phases are considered to exist because of the analogy of the TEM images for Sample A shown in Figure 4, owing to the same deposition temperature for the Mn 2 VAl layer. Although Sample C shows no net magnetization because of the possible antiferromagnetism [9,24,25], the Mn-moments aligned by H exhibit XMCD with peak-splitting around the L 3 -edge, which is similar to the fully-ordered Mn 2 VAl samples in previous studies [19,21,32]. For both cases of Samples C and D, no hysteresis is observed for the ESMHs shown in Figure 8, which implies that there is no spontaneous magnetization in the samples.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Our previous work revealed that a half-metallic full-Heusler Mn 2 VAl compound is a promising p-type TE material [17]. Compared with other full-Heusler compounds, the Mn 2 VAl compound has an advantage that it can be easily prepared by various methods such as arc-melting [17,[19][20][21], spark-plasmasintering (SPS) [17], induction-melting [22,23], and ultra-high-vacuum magnetron sputtering technique [24][25][26]. A disadvantage of the Mn 2 VAl compound is its low PF=2.7×10 −4 Wm −1 K −2 at 717 K [17], being inferior to an n-type half-metallic full-Heusler Co 2 MnSi compound (2.9×10 −3 Wm −1 K −2 at 550 K [16]).…”
Section: Introductionmentioning
confidence: 99%